PENGEMBANGAN SILABUS MATERI AJAR BAHASA JEPANG UNTUK MENDUKUNG PEMBANGUNAN INDONESIA EMAS 2045 PADA SEKTOR PARIWISATA - Ni Putu Sasmika Dewi (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2025)
Development of Syllabus that focused on language competence development and an industry-oriented curriculum to support Indonesia’s Golden Era 2045 in the tourism sector is important to do. The syllabus development takes into account aspects of globalization, international competition, and workforce competitiveness. This research utilizes the 4D model of Thiagarajan’s Research and Development method, with data collected through structured interviews, participatory observation, questionnaires, expert validation, and teaching trials. Needs analysis results indicate that the materials taught so far have been limited to characters and grammar, without direction towards the tourism industry. Additionally, the number of credits (SKS) provided has been insufficient, making it difficult to integrate Japanese culture and language into the learning process. Based on data analyzed using Gregory’s formula, the syllabus was found to have very high validity from experts with a score of 12/12=1, indicating that further development is highly feasible. The implementation feasibility reached 99.13%, showing that this syllabus is highly suitable for use in Japanese language teaching. This syllabus has the potential to strengthen sustainable tourism human resources, improve students' Japanese language competence, and enhance their competitiveness in facing Indonesia’s Golden Era 2045 in the tourism sector.